IMPLEMENTASI FSM SEBAGAI RESPON OTONOM DAN ADAPTIF NPC PADA GAME “AWANG MENJELAJAHI KOTA TENGGARONG” - Azahari Azahari; Ivan Haristyawan; Muhammad Jariansyah (Jurnal Ilmiah Matrik, 2020)
Development of the game towards a tourist promotion tool is very important. The game "Awang exploring the City of Tenggarong" is an android smartphone game that tells the story of a tourist / traveler named Awang who roams every tourist destination in the Tenggarong City. The development of this game uses multimedia development life cycle, starting from the concept, assembly, and testing. Artificial intelligence is also needed in the development of this game. Players will be accompanied by NPC (Non Player Character) in the form of a female tour guide. NPCs equipped with the Finite State Machine (FSM) model can guide players to go to each Tenggarong tourist attraction, and it can also provide information related to these tourist attractions. The final result of this research is a game that can be a media for tourism promotion in Tenggarong city